Collaborative Governance dalam Penanggulangan Pandemi Covid-19 di Kota Tanjungpinang - Faizal Rianto; Rendra Setyadiharja (STISIPOL Raja Haji, 2026)
The Covid-19 pandemic is a public health crisis that demands a swift and effective policy response, but it cannot be optimally addressed by government actors alone. Previous studies have shown that collaboration between government and non-government actors is a key factor in successfully managing the pandemic. The research problem in this study is the involvement and roles of government and non-government actors in managing the Covid-19 pandemic in Tanjungpinang, as well as the contribution of collaboration between actors to the effectiveness of policy responses. This study aims to map, analyze, and elaborate on the roles of government and non-government actors in managing the Covid-19 pandemic in Tanjungpinang. This study uses a qualitative approach with a case study design, through in-depth interviews, documentation studies, and secondary data analysis. The results show that the success of managing the Covid-19 pandemic in Tanjungpinang is determined not only by the role of the government but also by collaboration with non-government actors, such as community organizations, religious institutions, local communities, and the private sector. This collaboration plays a crucial role in policy coordination, resource mobilization, and the implementation of vaccinations and health outreach.